(untitled) (REMUNOM, 2025)
This article investigates the conceptual and historical evolution of vegetation in urban environments, addressing everything from the initial inclusion of green areas in cities to the contemporary understanding of urban forests. The main focus is on the Brazilian reality, examining crucial moments of urban development that influenced the presence and function of green spaces. To this end, an in-depth bibliographic review was undertaken, prioritizing the contributions of national researchers on topics such as urban ecology, environmental planning, and tree planting itself. The purpose is to uncover the motivations that drove the creation and maintenance of urban greenery over time, analyzing the factors, paradigm shifts, and inherent tensions in the relationship between cities and their vegetative cover, culminating in the current appreciation of urban forests as a vital component of urban infrastructure.